PENGARUH SIKAP, NORMA SUBJEKTIF DAN KONTROL PERILAKU TERHADAP NIAT KEPATUHAN MUZAKKI PEGAWAI NEGERI SIPIL (PNS) DALAM MEMBAYAR ZAKAT PROFESI PADA BADAN AMIL ZAKAT (BAZ) KABUPATEN SUMENEP” - Fatati Nuryana (Research Institute and Community Engagement of IAIN MADURA, 2016)
The Existence of the charity is the way to collecting alms, including alms profession. The organization to intermediary between Muzakki and Mustahik, taking role in collect, distribute and utilization of alms. Badan Amil Zakat (BAZ) Sumenep as an institution to collect alms from Muzakki of the civilian state apparatus, has not been effective in tapping the potential of alms. To optimize this institution, it’s need to know the some factors influence compliance of Muzakki from civilian state apparatus in paying alms profession of attitudes, subjective norms and control of Muzakki’s behavioral. The rank of civilian state apparatus’s Muzakki was added as a filter by using Analysis with Dummy Variable. Results indicate that subjective norms and control of Muzakki’s behavioral have a significant effect to intention Muzakki of civilian state apparatus compliance in paying alms profession, while attitudes have no significant effect.